Review of Research on Tooth Surface Error Control of Large CNC Gear Form Grinding - Zhiwei Chen; Shuang Ding; Zhanqun Song; Zhongyu Wang (Jixie chuandong)
Compared with the worm wheel gear grinding，gear form grinding is suitable for high efficiency grinding of large diameter and large modulus gears，despite difficulties concerning with grinding precision control，precise modification of tooth profile and precision detection in machine. Reviewing the research and development of gear form grinding tooth surface error control at home and abroad， the research achievements and existing problems at home and abroad in recent years from the three error sources which are the grinding wheel dressing system error，gear grinding system error and on-machine inspection system error are discussed， proposes directions and contents that need further research which are the construction of a closed-loop grinding system of “grinding wheel dressing，gear form grinding，on-machine evaluation of tooth surface error，reverse traceability of machine tool errors & error tracking compensation” and the realization of the improvement of grinding accuracy and dressing accuracy，carries out research on tooth surface error mapping modeling，tooth surface error on-machine evaluation and tooth surface error tracking correction method，and optimizes the on-machine inspection and compensation system. Being familiar with the research and development status of gear form grinding error compensation is beneficial to key technology breakthroughs in the development of high precision gear form grinding and gear testing equipment.